Perovskite solar cell and method for preparing perovskite solar cell
Patent Information
- Application Number
- CN202611139714.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-09-25
AI Technical Summary
[0004]本申请的主要目的在于提供一种钙钛矿太阳能电池和钙钛矿太阳能电池的制备方法,以解决现有技术中如何提升钙钛矿太阳能电池的效率的问题
[0019]应用本申请的技术方案,提供了一种钙钛矿太阳能电池。包括:基底、电子传输层、钙钛矿吸光层、界面修饰层、空穴传输层以及电极层,界面修饰层的材料包括金属卤化物掺杂的钙钛矿量子点,界面修饰层中的量子点与钙钛矿吸光层具有相同的晶体结构类型;空穴传输层位于界面修饰层远离钙钛矿吸光层的一侧;电极层位于空穴传输层远离界面修饰层的一侧。本申请在钙钛矿吸光层和空穴传输层之间引入界面修饰层,可以构建出连续且梯度化的能级排列,使空穴从吸光层向电极迁移所需跨越的能垒降低,从而降低空穴传输的势能障碍,同时界面修饰层钝化表面缺陷、抑制复合,从而加速光生载流子抽取速率;进一步地,界面修饰层的材料包括金属卤化物掺杂的钙钛矿量子点,由于金属离子的离子半径较小,其进入B位晶格可以引发局部晶格收缩,能够引起晶格收缩,增强八面体结构稳定性,以及晶体的结晶性;此外,界面修饰层中的量子点与钙钛矿吸光层具有相同的晶体结构类型,可以形成稳定界面,从而进一步减少由于离子迁移导致界面退化而产生新缺陷的可能。综合上述几种方式,可以协同提升钙钛矿太阳能电池的效率。
Smart Images

Figure CN122825637A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cells, and more specifically, to a perovskite solar cell and a method for preparing a perovskite solar cell. Background Technology
[0002] Perovskite materials have attracted much attention due to their advantages such as high light absorption coefficient, high defect tolerance, bipolar charge transfer, broad absorption spectrum, long carrier diffusion length, low exciton binding energy, and tunable band gap. How to further improve their efficiency is an urgent problem to be solved.
[0003] The information disclosed above in the background section is only intended to enhance the understanding of the background art of the art described herein. Therefore, the background art may contain certain information that does not constitute prior art known to those skilled in the art in this country. Summary of the Invention
[0004] The main objective of this application is to provide a perovskite solar cell and a method for fabricating a perovskite solar cell, in order to solve the problem of how to improve the efficiency of perovskite solar cells in the prior art.
[0005] To achieve the above objectives, according to one aspect of this application, a perovskite solar cell is provided, comprising: a substrate; an electron transport layer located on one side of the substrate; a perovskite light-absorbing layer located on the side of the electron transport layer away from the substrate; an interface modification layer located on the side of the perovskite light-absorbing layer away from the electron transport layer, the interface modification layer being made of metal halide-doped perovskite quantum dots, the quantum dots in the interface modification layer having the same crystal structure type as the perovskite light-absorbing layer; a hole transport layer located on the side of the interface modification layer away from the perovskite light-absorbing layer; and an electrode layer located on the side of the hole transport layer away from the interface modification layer.
[0006] Optionally, the thickness of the interface modification layer is 1~3nm.
[0007] Optionally, the metal halide includes at least one of nickel bromide, tin bromide, and lanthanum bromide.
[0008] Optionally, the interface modification layer satisfies at least one of the following: the lattice constant of the interface modification layer is 5.80~5.95 Å; the octahedral distortion of the interface modification layer is 2°~9°.
[0009] Optionally, the perovskite quantum dots satisfy at least one of the following: the average particle size of the perovskite quantum dots is 3~15nm; the standard deviation of the particle size distribution of the perovskite quantum dots is less than or equal to 5nm.
[0010] Optionally, the perovskite quantum dots satisfy at least one of the following: the full width at half maximum (FWHM) of the characteristic peaks of the perovskite quantum dots is 15 nm to 27 nm; the crystallinity of the perovskite quantum dots is 85% to 95%.
[0011] Optionally, the perovskite quantum dot satisfies at least one of the following: the concentration of halogen vacancies on the surface of the perovskite quantum dot is less than or equal to 1 × 10⁻⁶. 16 cm -3 The surface defect state density of the perovskite quantum dots is less than or equal to 5 × 10⁻⁶. 11 cm -2 eV -1 .
[0012] Optionally, the thickness of the core-shell structure of the perovskite quantum dots is 1~10 nm.
[0013] Optionally, in the interface modification layer, the mass ratio of the metal halide to the perovskite quantum dot is 1:(6~15).
[0014] To achieve the above objectives, according to another aspect of this application, a method for fabricating a perovskite solar cell is provided. The method is used to fabricate any of the aforementioned solar cells. The method includes: providing a substrate; forming an electron transport layer on one side of the substrate; forming a perovskite light-absorbing layer on the side of the electron transport layer away from the substrate; forming an interface modification layer on the side of the perovskite light-absorbing layer away from the electron transport layer, wherein the material of the interface modification layer comprises metal halide-doped perovskite quantum dots, and the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer; and sequentially forming a hole transport layer and an electrode layer on the side of the interface modification layer away from the perovskite light-absorbing layer.
[0015] Optionally, an interface modification layer is formed on the side of the perovskite light-absorbing layer away from the electron transport layer, comprising: providing a modification solution, wherein the modification solution comprises the metal halide, the perovskite quantum dot material, and an orthogonal solvent; spin-coating the modification solution onto the surface of the perovskite light-absorbing layer away from the electron transport layer, and performing an annealing treatment to obtain the interface modification layer.
[0016] Optionally, a modification solution is provided, comprising: providing a predetermined hydrate, the predetermined hydrate comprising the metal halide; dissolving the predetermined hydrate, AX, and BX2 in the orthogonal solvent to obtain a third precursor solution, and adding oleic acid and oleylamine to the third precursor solution to obtain a fourth precursor solution; and injecting the fourth precursor solution into a toluene solution to obtain the modification solution.
[0017] Optionally, the fourth precursor solution is injected into a toluene solution to obtain a modified solution, comprising: stirring the fourth precursor solution at a first predetermined speed, and then injecting it into a predetermined volume of the toluene solution to obtain a first preparative solution, wherein the first predetermined speed is 1000~1200 rpm and the predetermined volume is 5~10 mL; centrifuging the first preparative solution at a second predetermined speed for a first predetermined time to obtain a precipitate, wherein the second predetermined speed is 7000~8000 rpm and the first predetermined time is 3~5 min; washing the precipitate with a washing solvent and centrifuging it at a third predetermined speed for a second predetermined time to obtain the modified solution, wherein the washing solvent includes toluene and ethyl acetate, the third predetermined speed is 4000~8000 rpm and the second predetermined time is 3~5 min.
[0018] Optionally, the modification solution is spin-coated onto the surface of the perovskite light-absorbing layer on the side away from the electron transport layer, and then annealed to obtain the interface modification layer. This includes: spin-coating the modification solution onto the surface of the perovskite light-absorbing layer on the side away from the electron transport layer at a fourth predetermined rotation speed for a third predetermined duration, wherein the fourth predetermined rotation speed is 1000~2000 rpm and the third predetermined duration is 15~30 s; and annealing at a predetermined temperature for a fourth predetermined duration, wherein the predetermined temperature is 150~200℃ and the fourth predetermined duration is 8~10 min.
[0019] This application provides a perovskite solar cell. It includes: a substrate, an electron transport layer, a perovskite light-absorbing layer, an interface modification layer, a hole transport layer, and an electrode layer. The interface modification layer is made of metal halide-doped perovskite quantum dots, and the quantum dots in the interface modification layer have the same crystal structure as the perovskite light-absorbing layer. The hole transport layer is located on the side of the interface modification layer away from the perovskite light-absorbing layer. The electrode layer is located on the side of the hole transport layer away from the interface modification layer. This application introduces an interface modification layer between the perovskite light-absorbing layer and the hole transport layer, which can construct a continuous and gradient energy level arrangement, reducing the energy barrier required for holes to migrate from the light-absorbing layer to the electrode, thereby lowering the potential energy barrier for hole transport. Simultaneously, the interface modification layer passivates surface defects and suppresses recombination, thus accelerating the photogenerated carrier extraction rate. Furthermore, the interface modification layer is made of perovskite quantum dots doped with metal halides. Due to the small ionic radius of metal ions, their entry into the B-site lattice can induce local lattice contraction, enhancing the stability of the octahedral structure and the crystallinity of the crystal. In addition, the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer, forming a stable interface, further reducing the possibility of new defects generated due to interface degradation caused by ion migration. Combining these methods, the efficiency of perovskite solar cells can be synergistically improved. Attached Figure Description
[0020] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:
[0021] Figure 1 A schematic diagram of the structure of a perovskite solar cell provided according to an embodiment of this application is shown;
[0022] Figure 2 A schematic flowchart of a method for fabricating a perovskite solar cell according to an embodiment of this application is shown.
[0023] The above figures include the following reference numerals:
[0024] 10. Substrate; 11. Electron transport layer; 12. Perovskite light-absorbing layer; 13. Interface modification layer; 14. Hole transport layer; 15. Electrode layer. Detailed Implementation
[0025] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0026] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0027] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate for the embodiments of the invention described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0028] It should be understood that when an element (such as a layer, film, region, or substrate) is described as being "on" another element, the element may be directly on the other element, or there may be an intermediate element present. Furthermore, in the specification and claims, when an element is described as being "connected" to another element, the element may be "directly connected" to the other element, or "connected" to the other element via a third element.
[0029] As described in the background section, in order to address the problem of how to improve the efficiency of perovskite solar cells in the prior art, embodiments of this application provide a perovskite solar cell and a method for fabricating a perovskite solar cell.
[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.
[0031] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell provided in an embodiment of this application. (As shown...) Figure 1 As shown, it includes:
[0032] Base 10;
[0033] Perovskite solar cells (PSCs) are a novel type of photovoltaic device that uses organic-inorganic hybrid halide perovskite materials as the light-absorbing layer. They possess advantages such as high absorption coefficient, long carrier diffusion length, solution-processability, and tunable bandgap. The substrate 10 can provide mechanical support and can be made of materials such as glass, flexible PET / PI film, or metal foil. A transparent substrate 10 facilitates the transmission of incident light.
[0034] An electron transport layer 11 is located on one side of the substrate 10.
[0035] The electron transport layer 11 can be made of materials such as TiO2, SnO2, ZnO, or PCBM.
[0036] The perovskite light-absorbing layer 12 is located on the side of the electron transport layer 11 away from the substrate 10.
[0037] The perovskite light-absorbing layer 12 can be made of ABX3 perovskite material. Under illumination, the perovskite light-absorbing layer 12 generates electron-hole pairs; electrons are extracted by the electron transport layer 11 and transported to the cathode; holes are extracted by the hole transport layer 14 and transported to the anode; and current is formed through the external circuit.
[0038] The interface modification layer 13 is located on the side of the perovskite light-absorbing layer 12 away from the electron transport layer 11. The material of the interface modification layer 13 includes metal halide-doped perovskite quantum dots. The quantum dots in the interface modification layer 13 have the same crystal structure type as the perovskite light-absorbing layer 12.
[0039] The interface modification layer 13 is used to passivate perovskite surface defects, reduce non-radiative recombination, regulate energy level arrangement, and improve carrier extraction efficiency.
[0040] Hole transport layer 14 is located on the side of the interface modification layer 13 away from the perovskite light-absorbing layer 12.
[0041] Hole transport layer 14 can be made of Spiro-OMeTAD, PTAA, PEDOT:PSS, NiO x Materials such as CuSCN.
[0042] The electrode layer 15 is located on the side of the hole transport layer 14 away from the interface modification layer 13.
[0043] The electrode layer 15 is used to collect charge carriers and output current, and can be made of materials such as Au, Ag, and Cu.
[0044] This embodiment provides a perovskite solar cell. It includes: a substrate, an electron transport layer, a perovskite light-absorbing layer, an interface modification layer, a hole transport layer, and an electrode layer. The interface modification layer is made of metal halide-doped perovskite quantum dots, and the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer. The hole transport layer is located on the side of the interface modification layer away from the perovskite light-absorbing layer. The electrode layer is located on the side of the hole transport layer away from the interface modification layer. This application introduces an interface modification layer between the perovskite light-absorbing layer and the hole transport layer, which can construct a continuous and gradient energy level arrangement, reducing the energy barrier required for holes to migrate from the light-absorbing layer to the electrode, thereby lowering the potential energy barrier for hole transport. Simultaneously, the interface modification layer passivates surface defects and suppresses recombination, thus accelerating the photogenerated carrier extraction rate. Furthermore, the interface modification layer is made of perovskite quantum dots doped with metal halides. Due to the small ionic radius of metal ions, their entry into the B-site lattice can induce local lattice contraction, enhancing the stability of the octahedral structure and the crystallinity of the crystal. In addition, the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer, forming a stable interface, further reducing the possibility of new defects generated due to interface degradation caused by ion migration. Combining these methods, the efficiency of perovskite solar cells can be synergistically improved.
[0045] In practice, the thickness of the interface modification layer is 1-3 nm. This thickness range provides good passivation and reduces non-radiative recombination, while also preventing excessive thickness from negatively impacting the overall thickness of the perovskite solar cell.
[0046] In some embodiments, the metal halide includes at least one selected from nickel bromide, tin bromide, and lanthanum bromide. Ni² in the metal halide + Sn 4+ 、Ln³ + Plasma doping can induce lattice contraction, making the doped octahedral structure more stable, enhancing the structural stability of quantum dots, and inhibiting quantum dot aggregation. It also helps to enhance crystallinity, improve internal defects, and reduce nonradiative recombination caused by defects. Furthermore, the introduction of Br... - Able to react with cations (such as Pb²) on the surface of quantum dots + Coordination reduces the formation of halogen vacancies and passivates surface defects.
[0047] The metal ions (Ni²) in these metal halides + Sn 4+ 、Ln³ + The ionic radius of Pb²⁺ is relatively small, and it can be introduced into the lattice of perovskite quantum dots as a B-site dopant ion to replace some of the original B-site ions (such as Pb²⁺).+ This causes lattice contraction.
[0048] In other embodiments, the interface modification layer satisfies at least one of the following: the lattice constant of the interface modification layer is 5.80~5.95 Å; the octahedral distortion of the interface modification layer is 2°~9°. The lattice constant of the interface modification layer being in the range of 5.80~5.95 Å indicates that the interface modification layer and the perovskite light-absorbing layer have good lattice matching, which is beneficial for forming epitaxial growth or close contact at the interface, reducing interface defects and stress caused by lattice mismatch. The octahedral distortion of the interface modification layer being in the above range indicates that after metal halide doping, the octahedral structure maintains appropriate symmetry and good structural stability, which is beneficial for suppressing structural phase transitions or decomposition caused by external factors such as heat, light, water, and oxygen. The combined good lattice and chemical compatibility can form a stable interface, reducing the possibility of new defects caused by interface degradation due to ion migration, thereby improving the long-term stability of the device.
[0049] In practical applications, lattice constant and octahedral distortion are important parameters for characterizing the perovskite crystal structure, directly reflecting the lattice matching degree and structural stability between the interface modification layer and the underlying perovskite light-absorbing layer. The lattice constant of the interface modification layer can be any one of 5.80 Å, 5.85 Å, 5.90 Å, or 5.95 Å, or any value between any two of these values; the octahedral distortion of the interface modification layer can be any one of 2°, 4°, 5°, 7°, 8°, or 9°, or any value between any two of these values.
[0050] In some embodiments, the perovskite quantum dots satisfy at least one of the following: the average particle size of the perovskite quantum dots is 3-15 nm; the standard deviation of the particle size distribution of the perovskite quantum dots is less than or equal to 5 nm. An average particle size within this range allows the quantum dots to be located in a strong quantum confinement region, enabling the transformation of continuous energy levels into discrete energy levels, and tunable band gaps. This is beneficial for optimizing the energy level arrangement at the interface and improving the extraction efficiency of photogenerated carriers. Simultaneously, the smaller particle size gives the quantum dots a large specific surface area, which is beneficial for fully covering and passivating surface defects in the perovskite light-absorbing layer at the interface. A standard deviation of the particle size distribution within the above range indicates good uniformity of quantum dot size, ensuring the consistency of the interface modification layer's performance and avoiding optical performance fluctuations and interface energy level disorder caused by uneven quantum dot dispersion.
[0051] In practical implementation, particle size is a core parameter of quantum dot materials, which can determine the strength of the quantum confinement effect and the size of the optical band gap. The average particle size of the perovskite quantum dots can be any one of 3nm, 6nm, 9nm, 12nm, and 15nm, or it can be between any two of the above values; the standard deviation of the particle size distribution of the perovskite quantum dots can be any one of 2nm, 3nm, 4nm, and 5nm, or it can be between any two of the above values.
[0052] In other embodiments, the perovskite quantum dots satisfy at least one of the following: the full width at half maximum (FWHM) of the characteristic peak of the perovskite quantum dots is 15 nm to 27 nm; the crystallinity of the perovskite quantum dots is 85% to 95%. The FWHM of the characteristic peak of the perovskite quantum dots being within the above range indicates that the quantum dots have a relatively concentrated size distribution and excellent optical performance, which is beneficial for the interface modification layer to play a stable and consistent role in light absorption and carrier transport. The crystallinity of the perovskite quantum dots being within the above range indicates that the internal lattice arrangement of the quantum dots is regular, and there are fewer internal crystal defects (such as dislocations, grain boundaries, vacancies, etc.), which can effectively reduce nonradiative recombination caused by bulk defects, improve carrier lifetime and the passivation effect of the interface modification layer. At the same time, higher crystallinity also helps to enhance the structural stability and resistance to water and oxygen erosion of the quantum dots.
[0053] It should be noted that the full width at half maximum (FWHM) of the characteristic peaks of perovskite quantum dots can reflect the uniformity of the quantum dot size distribution and spectral purity; the crystallinity of perovskite quantum dots can reflect the perfection of the internal crystal structure of the quantum dots. The FWHM of the characteristic peaks of the aforementioned perovskite quantum dots can be any one of 15 nm, 17 nm, 20 nm, or 27 nm, or it can be located between any two of the above values; the crystallinity of the aforementioned perovskite quantum dots can be any one of 85%, 90%, or 95%, or it can be located between any two of the above values.
[0054] In some embodiments, the perovskite quantum dots satisfy at least one of the following: the concentration of halogen vacancies on the surface of the perovskite quantum dots is less than or equal to 1 × 10⁻⁶. 16 cm -3 The surface defect state density of the above perovskite quantum dots is less than or equal to 5 × 10⁻⁶. 11 cm -2 eV -1 The concentration of halogen vacancies on the surface of perovskite quantum dots falls within the aforementioned range. This allows for a lower concentration of halogen vacancies on the surface of the perovskite quantum dots, indicating that the quantum dot surface is rich in halide ions, which can suppress Pb loss caused by halogen deficiency. 0The formation of defects and deep-level trap states; the surface defect state density of perovskite quantum dots is within the aforementioned range, which allows for a low surface defect state density. This means that the interface modification layer itself has an extremely low non-radiative recombination center density, passivating the surface defects of the perovskite light-absorbing layer without introducing new recombination channels. Effective passivation of surface defects can enhance radiative recombination efficiency, improve the open-circuit voltage and fill factor of perovskite solar cells, and also help improve the fluorescence quantum yield and photostability of the quantum dots themselves.
[0055] In the above implementation process, halogen vacancies and surface defect states are two types of surface defects in perovskite quantum dots, and are the main causes of nonradiative recombination. The concentration of halogen vacancies on the surface of the perovskite quantum dots can be 1 × 10⁻⁶. 14 cm -3 1×10 15 cm -3 1×10 16 cm -3 Any one of the above values, or any two of the above values; the surface defect state density of the above perovskite quantum dots can be 2 × 10⁻⁶. 11 cm -2 eV -1 3×10 11 cm -2 eV -1 4×10 11 cm -2 eV -1 5×10 11 cm -2 eV -1 Any one of the above values can also be located between any two of the above values.
[0056] In some other embodiments, the thickness of the core-shell structure of the perovskite quantum dots is 1-10 nm. A core-shell structure thickness within this range provides sufficient protection without completely shielding the quantum confinement effect or hindering carrier tunneling due to excessive shell thickness.
[0057] The core-shell structure of perovskite quantum dots is formed during metal halide doping by excess Br. - With Pb² + The perovskite quantum dot core is formed by encapsulating it with a PbBr2 compound shell that reacts on the surface of the quantum dot. The shell effectively blocks the intrusion of external water molecules and oxygen, protecting the internal perovskite quantum dot core from water and oxygen erosion and decomposition, thereby improving the environmental stability of the quantum dot and the long-term operational stability of the device. Furthermore, the core-shell structure also helps to suppress direct contact and aggregation between quantum dots, maintaining a uniform dispersion of the quantum dots in the interface modification layer.
[0058] In some embodiments, the mass ratio of the metal halide to the perovskite quantum dots in the interface modification layer is 1:(6~15). A mass ratio of metal halide to perovskite quantum dots within this range ensures adequate metal halide doping, effectively inducing lattice shrinkage, enhancing octahedral structure stability and crystallinity, while avoiding phase separation, excessive lattice distortion, or deterioration of quantum dot optical properties due to excessive doping.
[0059] In the above implementation process, the mass ratio of metal halide to the perovskite quantum dot reflects the proportion of metal halide dopant relative to the perovskite quantum dot substrate, directly affecting the doping effect and the photoelectric performance of the quantum dot. An appropriate doping ratio ensures that the interface modification layer maintains a crystal structure and band structure similar to the perovskite light-absorbing layer, guaranteeing lattice matching and energy level continuity at the interface. This ratio range balances improving the structural stability of the quantum dot with maintaining its photoelectric performance, ensuring that the interface modification layer, while passivating defects and modulating energy levels, does not negatively impact light absorption and carrier transport.
[0060] In the above implementation process, the perovskite solar cell satisfies at least one of the following: the material of the hole transport layer includes carbon; the material of the electrode layer includes carbon. This configuration can further reduce the fabrication cost of perovskite solar cells while simplifying the process steps.
[0061] In practical applications, the hole transport layer and electrode layer can be printed in one step, eliminating the need for step-by-step deposition of the hole transport layer and electrode layer, which can further save process steps.
[0062] According to another embodiment of this application, a method for preparing a perovskite solar cell is also provided. This method is used to prepare any of the aforementioned solar cells. Figure 2 This is a schematic flowchart illustrating the fabrication method of a perovskite solar cell provided in an embodiment of this application. Figure 2 As shown, the above method includes:
[0063] Step S201, provide a substrate;
[0064] Step S202: An electron transport layer is formed on one side of the substrate.
[0065] Step S203: A perovskite light-absorbing layer is formed on the side of the electron transport layer away from the substrate.
[0066] Step S204: An interface modification layer is formed on the side of the perovskite light-absorbing layer away from the electron transport layer. The material of the interface modification layer includes metal halide-doped perovskite quantum dots, and the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer.
[0067] In step S205, a hole transport layer and an electrode layer are sequentially formed on the side of the interface modification layer away from the perovskite light-absorbing layer.
[0068] The substrate described above can be either rigid or flexible. An electron transport layer can be formed on one side of the substrate using a solution spin-coating method. In practical applications, a perovskite light-absorbing layer can be formed on the side of the electron transport layer away from the substrate using a one-step, two-step, vapor deposition, or coating method. Quantum dot material and perovskite material doped with predetermined elements can be deposited sequentially. The hole transport layer can be formed using spin-coating, sputtering, or other methods. An electrode layer can also be formed using thermal evaporation, sputtering, or other methods. Alternatively, both the hole transport layer and the electrode layer can be formed simultaneously.
[0069] This embodiment provides a method for fabricating a perovskite solar cell. First, a substrate is provided; then, an electron transport layer is formed on one side of the substrate; a perovskite light-absorbing layer is formed on the side of the electron transport layer away from the substrate; next, an interface modification layer is formed on the side of the perovskite light-absorbing layer away from the electron transport layer. The interface modification layer is made of quantum dot material and perovskite material doped with a predetermined element, including at least one of manganese, nickel, tin, and lanthanides; finally, a hole transport layer and an electrode layer are sequentially formed on the side of the interface modification layer away from the perovskite light-absorbing layer. This application introduces an interface modification layer between the perovskite light-absorbing layer and the hole transport layer, which can result in a more suitable energy level arrangement, reduce the interface barrier, and accelerate the photogenerated carrier extraction rate. Furthermore, the interface modification layer material includes metal halide-doped perovskite quantum dots, which can induce lattice contraction, enhance the stability of the octahedral structure, and improve the crystallinity of the crystal. Combining these two methods can synergistically improve the efficiency of the perovskite solar cell.
[0070] To further improve the stability of the electron transport layer, step S202 can be achieved through the following steps: step S2021, forming a dense layer on one side of the substrate; step S2022, forming a mesoporous layer on the side of the dense layer away from the substrate, wherein the dense layer and the mesoporous layer form the electron transport layer, and the density of the dense layer is greater than the density of the mesoporous layer.
[0071] The aforementioned dense layer is a non-porous, continuous, and dense thin film, typically with a thickness of 50–150 nm. The mesoporous layer is a porous, nanostructured thin film deposited on top of the dense layer; its pore size can be 10–30 nm, and its thickness can be 200–500 nm. The materials of the dense layer and the mesoporous layer can be the same or different. The specific preparation method of the above-mentioned dense layer is as follows: First, prepare a TiO2 precursor solution for the dense layer by mixing isopropyl titanate, anhydrous ethanol, and concentrated hydrochloric acid in a volume ratio of 40 μL: 1 mL: 8 μL, stirring and filtering for later use; then, spin-coat the solution onto a prepared FTO conductive glass etching substrate at a spin speed of 3000 rpm for 30 s; next, anneal the sample on a hot plate at 150℃ for 15 min, repeating this process twice; after removing the adhesive tape, anneal the sample in a muffle furnace at 500℃ for 30 min, and remove it after cooling; then, immerse the sample in a 0.04 mol / L TiCl4 aqueous solution and keep it in a 70℃ oven for 30 min; finally, wash the sample with deionized water and dry it, then anneal it again in a muffle furnace at 500℃ for 30 min, and remove it after cooling, thus completing the preparation of the dense layer. The specific preparation method of the above-mentioned mesoporous layer is as follows: TiO2 slurry is dissolved in anhydrous ethanol at a mass ratio of 1:4 and stirred for 8-12 hours; then, it is spin-coated onto the above-mentioned dense TiO2 layer at a spin-coating speed of 5000 rpm for 30 seconds; next, it is kept at 80°C for 40 minutes in an oven and annealed in a muffle furnace at 500°C for 30 minutes, and then removed after cooling; then, it is immersed in a TiCl4 aqueous solution with a concentration of 0.02 mol / L and kept at 70°C for 30 minutes; finally, it is washed with deionized water and dried, and then annealed again in a muffle furnace at 500°C for 30 minutes, and then removed after cooling, thus completing the preparation of the mesoporous layer.
[0072] The above implementation scheme, specifically step S203, can be achieved through the following steps: Step S2031, providing a first precursor solution and a second precursor solution, wherein the first precursor solution comprises BX2 and N,N-dimethylformamide, and the second precursor solution comprises AB and methanol; Step S2032, spin-coating the first precursor solution onto the surface of the electron transport layer away from the substrate, and performing an annealing treatment; Step S2033, spin-coating the second precursor solution onto the surface of the electron transport layer away from the substrate, and performing an annealing treatment to obtain the perovskite light-absorbing layer, wherein the material of the perovskite light-absorbing layer comprises ABX3. This method can further prepare a perovskite light-absorbing layer with good performance.
[0073] Taking the CsPbBr3 perovskite light-absorbing layer as an example, the specific preparation steps of the perovskite light-absorbing layer are as follows: First, the structure after the formation of the electron transport layer is cleaned with a 50W plasma cleaner for 2 minutes; then, a certain concentration of PbBr2 / DMF solution is prepared, and after being dissolved by constant temperature stirring in a 70℃ oil bath, it is spin-coated onto the sample at 2000 rpm for 30 seconds, and then annealed on a 90℃ hot plate for 30 minutes; finally, the prepared CsBr / methanol solution is spin-coated onto the sample and annealed on a 250℃ hot plate for 5 minutes. This process is repeated 5 times to complete the preparation of the CsPbBr3 perovskite light-absorbing layer.
[0074] In some embodiments, step S204 can also be implemented in other ways, such as: step S2041, providing a modification solution, wherein the modification solution includes the metal halide, the perovskite quantum dot material, and an orthogonal solvent; step S2042, spin-coating the modification solution onto the surface of the perovskite light-absorbing layer away from the electron transport layer, and performing an annealing treatment to obtain the interface modification layer. The above methods can further improve the passivation effect of the interface modification layer, thereby further reducing non-radiative recombination.
[0075] In the above implementation scheme, step S2041 can be achieved in the following manner: Step S20411, providing a predetermined hydrate, the predetermined hydrate including the aforementioned metal halide; Step S20412, dissolving the predetermined hydrate, AX, and BX2 in the aforementioned orthogonal solvent to obtain a third precursor solution, and adding oleic acid and oleylamine to the aforementioned third precursor solution to obtain a fourth precursor solution; Step S20413, injecting the aforementioned fourth precursor solution into a toluene solution to obtain the aforementioned modified solution. The above method can further improve the reliability of the aforementioned modified solution.
[0076] Step S20413 can be implemented through the following steps: Step S204131, stirring the fourth precursor solution at a first predetermined speed, and then injecting it into a predetermined volume of the toluene solution to obtain a first preparative solution, wherein the first predetermined speed is 1000~1200 rpm and the predetermined volume is 5~10 mL; Step S204132, centrifuging the first preparative solution at a second predetermined speed for a first predetermined time to obtain a precipitate, wherein the second predetermined speed is 7000~8000 rpm and the first predetermined time is 3~5 min; Step S204133, washing the precipitate with a washing solvent and centrifuging at a third predetermined speed for a second predetermined time to obtain the modified solution, wherein the washing solvent includes toluene and ethyl acetate, the third predetermined speed is 4000~8000 rpm and the second predetermined time is 3~5 min. The above method can further improve the reliability of the modified solution.
[0077] In some embodiments, step S2042 can be implemented by other steps, such as: step S20421, spin-coating the modification solution onto the surface of the perovskite light-absorbing layer away from the electron transport layer at a fourth predetermined rotation speed, and continuing for a third predetermined duration, wherein the fourth predetermined rotation speed is 1000~2000 rps and the third predetermined duration is 15~30 s; step S20422, annealing at a predetermined temperature and continuing for a fourth predetermined duration, wherein the predetermined temperature is 150~200℃ and the fourth predetermined duration is 8~10 min. The above method can further improve the stability of the interface modification layer.
[0078] With CsPb (x) Mn (1-x) Taking the Br3PQD interface modification layer as an example, the preparation steps of the interface modification layer are as follows: First, dissolve MnBr2·4H2O (9mg), PbBr2 (0.2mmol), and CsBr (0.2mmol) in DMF (5mL) to obtain a precursor solution. Then, add OAm (0.25mL) and OA (0.5mL) to the above precursor solution and stir until the solution becomes clear. Take 1mL of the above solution and slowly inject it into 10mL of toluene solution while stirring vigorously at 1200rpm. After about 5s, the solution turns bright green, which indicates that CsPb has been obtained. (x) Mn (1-x) Br3PQD solution. CsPb (x) Mn (1-x)The Br3PQD solution needs to be purified before use: first, centrifuge at 8000 rpm for 5 min to collect the precipitate, then wash with a toluene / ethyl acetate mixture (1:3 volume ratio), and finally centrifuge at 5000 rpm for 5 min to obtain the purified QDs. Disperse the QDs in toluene solution and spin-coat them onto the surface of a CsPbBr3 perovskite film at 2000 rpm for 30 s. Afterward, anneal on a hot plate at 200°C for 10 min to complete the CsPb... (x) Mn (1-x) Preparation of Br3PQD interface modification layer.
[0079] In other embodiments, step S205 can be implemented by the following steps: Step S2051, a slurry is coated on the side of the interface modification layer away from the perovskite light-absorbing layer to obtain the hole transport layer and the electrode layer, wherein the slurry includes carbon. This method can further reduce the fabrication cost of perovskite solar cells while simplifying the process steps.
[0080] The specific steps for forming the hole transport layer and the above-mentioned electrode layer are as follows: Use a carbon scraper to directly align the perovskite film with the template with the pre-made electrode shape, use a spatula to evenly scrape carbon slurry onto the perovskite film, and anneal the sample with the scraped carbon at 120°C for 15 minutes to complete the preparation of the hole transport layer and the above-mentioned electrode layer.
[0081] To enable those skilled in the art to better understand the technical solution of this application, the perovskite solar cell of this application will be described in detail below with reference to specific embodiments.
[0082] Example 1
[0083] This embodiment relates to a specific perovskite solar cell, including:
[0084] Base;
[0085] An electron transport layer is located on one side of the aforementioned substrate;
[0086] The perovskite light-absorbing layer is located on the side of the electron transport layer away from the substrate.
[0087] An interface modification layer is located on the side of the perovskite light-absorbing layer away from the electron transport layer. The material of the interface modification layer includes manganese bromide-doped perovskite quantum dots. The quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer.
[0088] The hole transport layer is located on the side of the interface modification layer away from the perovskite light-absorbing layer.
[0089] The electrode layer is located on the side of the hole transport layer away from the interface modification layer.
[0090] Example 2
[0091] This embodiment relates to a specific perovskite solar cell. The only difference between this embodiment and Embodiment 1 is that the material of the interface modification layer includes tin bromide-doped perovskite quantum dots.
[0092] Example 3
[0093] This embodiment relates to a specific perovskite solar cell. The only difference between this embodiment and Embodiment 1 is that the material of the interface modification layer includes lanthanum bromide-doped perovskite quantum dots.
[0094] Example 4
[0095] This embodiment relates to a specific perovskite solar cell. The only difference between this embodiment and Embodiment 1 is that the material of the interface modification layer includes nickel bromide-doped perovskite quantum dots.
[0096] Comparative Example 1
[0097] This embodiment relates to a specific perovskite solar cell. The only difference between this embodiment and Embodiment 1 is that the material of the interface modification layer includes hydrogen bromide-doped perovskite quantum dots.
[0098] Comparative Example 2
[0099] This embodiment relates to a specific perovskite solar cell. The only difference between this embodiment and Embodiment 1 is that the material of the interface modification layer includes undoped perovskite quantum dots.
[0100] The performance of the perovskite solar cells using Examples 1-4 and Comparative Examples 1-2 was tested, and the test results are shown in Table 1:
[0101]
[0102] The experimental data above show that the photoelectric conversion efficiency of Examples 1 to 4 is higher than that of Comparative Examples 1 to 2, and the fill factor of Examples 1 to 4 is higher than that of Comparative Examples 1 to 2, indicating that the perovskite solar cell of this application can reduce carrier recombination loss and improve photoelectric conversion efficiency. The experimental data also show that the open-circuit voltage and short-circuit current of Examples 1 to 4 are higher than those of Comparative Examples 1 and 2, indicating that the solar cell of this application can improve the open-circuit voltage and short-circuit current of the perovskite solar cell.
[0103] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0104] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:
[0105] 1) The perovskite solar cell of this application. It comprises: a substrate, an electron transport layer, a perovskite light-absorbing layer, an interface modification layer, a hole transport layer, and an electrode layer. The electron transport layer is located on one side of the substrate; the perovskite light-absorbing layer is located on the side of the electron transport layer away from the substrate; the interface modification layer is located on the side of the perovskite light-absorbing layer away from the electron transport layer, and the material of the interface modification layer includes quantum dot materials and perovskite materials doped with predetermined elements, wherein the predetermined elements include at least one selected from manganese, nickel, tin, and lanthanides; the hole transport layer is located on the side of the interface modification layer away from the perovskite light-absorbing layer; and the electrode layer is located on the side of the hole transport layer away from the interface modification layer. This application introduces an interface modification layer between the perovskite light-absorbing layer and the hole transport layer, which can construct a continuous and gradient energy level arrangement, reducing the energy barrier required for holes to migrate from the light-absorbing layer to the electrode, thereby lowering the potential energy barrier for hole transport. Simultaneously, the interface modification layer passivates surface defects and suppresses recombination, thus accelerating the photogenerated carrier extraction rate. Furthermore, the interface modification layer is made of perovskite quantum dots doped with metal halides. Due to the small ionic radius of metal ions, their entry into the B-site lattice can induce local lattice contraction, enhancing the stability of the octahedral structure and the crystallinity of the crystal. In addition, the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer, forming a stable interface, further reducing the possibility of new defects generated due to interface degradation caused by ion migration. Combining these methods, the efficiency of perovskite solar cells can be synergistically improved.
[0106] 2) The method for fabricating the perovskite solar cell of this application. First, a substrate is provided; then, an electron transport layer is formed on one side of the substrate; a perovskite light-absorbing layer is formed on the side of the electron transport layer away from the substrate; then, an interface modification layer is formed on the side of the perovskite light-absorbing layer away from the electron transport layer. The material of the interface modification layer includes quantum dot materials and perovskite materials doped with predetermined elements, including at least one of manganese, nickel, tin, and lanthanides; finally, a hole transport layer and an electrode layer are sequentially formed on the side of the interface modification layer away from the perovskite light-absorbing layer. This application introduces an interface modification layer between the perovskite light-absorbing layer and the hole transport layer, which can construct a continuous and gradient energy level arrangement, reducing the energy barrier required for holes to migrate from the light-absorbing layer to the electrode, thereby lowering the potential energy barrier for hole transport. Simultaneously, the interface modification layer passivates surface defects and suppresses recombination, thus accelerating the photogenerated carrier extraction rate. Furthermore, the interface modification layer is made of perovskite quantum dots doped with metal halides. Due to the small ionic radius of metal ions, their entry into the B-site lattice can induce local lattice contraction, enhancing the stability of the octahedral structure and the crystallinity of the crystal. In addition, the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer, forming a stable interface, further reducing the possibility of new defects generated due to interface degradation caused by ion migration. Combining these methods, the efficiency of perovskite solar cells can be synergistically improved.
[0107] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A perovskite solar cell, characterized in that, include: Base; An electron transport layer is located on one side of the substrate; A perovskite light-absorbing layer is located on the side of the electron transport layer away from the substrate; An interface modification layer is located on the side of the perovskite light-absorbing layer away from the electron transport layer. The material of the interface modification layer includes metal halide-doped perovskite quantum dots, and the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer. A hole transport layer is located on the side of the interface modification layer away from the perovskite light-absorbing layer; The electrode layer is located on the side of the hole transport layer away from the interface modification layer.
2. The perovskite solar cell according to claim 1, characterized in that, The thickness of the interface modification layer is 1~3nm.
3. The perovskite solar cell according to claim 1, characterized in that, The metal halide includes at least one of nickel bromide, tin bromide, and lanthanum bromide.
4. The perovskite solar cell according to claim 1, characterized in that, The interface decoration layer satisfies at least one of the following: The lattice constant of the interface modification layer is 5.80~5.95 Å; The octahedral distortion of the interface modification layer is 2°~9°.
5. The perovskite solar cell according to claim 1, characterized in that, The perovskite quantum dot satisfies at least one of the following: The average particle size of the perovskite quantum dots is 3~15nm; The standard deviation of the particle size distribution of the perovskite quantum dots is less than or equal to 5 nm.
6. The perovskite solar cell according to claim 1, characterized in that, The perovskite quantum dot satisfies at least one of the following: The characteristic peak half-width of the perovskite quantum dots is 15 nm to 27 nm. The crystallinity of the perovskite quantum dots is 85%~95%.
7. The perovskite solar cell according to claim 1, characterized in that, The perovskite quantum dot satisfies at least one of the following: The concentration of halogen vacancies on the surface of the perovskite quantum dots is less than or equal to 1 × 10⁻⁶. 16 cm -3 ; The surface defect state density of the perovskite quantum dots is less than or equal to 5 × 10⁻⁶. 11 cm -2 eV -1 .
8. The perovskite solar cell according to claim 1, characterized in that, The thickness of the core-shell structure of the perovskite quantum dots is 1~10 nm.
9. The perovskite solar cell according to claim 1, characterized in that, In the interface modification layer, the mass ratio of the metal halide to the perovskite quantum dot is 1:(6~15).
10. A method for preparing a perovskite solar cell, characterized in that, The method is used to prepare the solar cell according to any one of claims 1 to 9, and the method includes: Provide a base; An electron transport layer is formed on one side of the substrate; A perovskite light-absorbing layer is formed on the side of the electron transport layer away from the substrate; An interface modification layer is formed on the side of the perovskite light-absorbing layer away from the electron transport layer. The material of the interface modification layer includes metal halide-doped perovskite quantum dots, and the quantum dots in the interface modification layer have the same crystal structure type as the perovskite light-absorbing layer. A hole transport layer and an electrode layer are sequentially formed on the side of the interface modification layer away from the perovskite light-absorbing layer.
11. The method for preparing a perovskite solar cell according to claim 10, characterized in that, An interface modification layer is formed on the side of the perovskite light-absorbing layer away from the electron transport layer, comprising: A modification solution is provided, wherein the modification solution comprises the metal halide, the perovskite quantum dot, and an orthogonal solvent; The modification solution is spin-coated onto the surface of the perovskite light-absorbing layer on the side away from the electron transport layer, and then annealed to obtain the interface modification layer.
12. The method for preparing a perovskite solar cell according to claim 11, characterized in that, Provide a modification solution, including: Provide a predetermined hydrate, the predetermined hydrate comprising the metal halide; The predetermined hydrate, AX, and BX2 are dissolved in the orthogonal solvent to obtain a third precursor solution, and oleic acid and oleylamine are added to the third precursor solution to obtain a fourth precursor solution; The fourth precursor solution is injected into a toluene solution to obtain the modified solution.
13. The method for preparing a perovskite solar cell according to claim 12, characterized in that, The fourth precursor solution is injected into a toluene solution to obtain a modified solution, comprising: The fourth precursor solution is stirred at a first predetermined speed, and then injected into a predetermined volume of the toluene solution to obtain a first preparative solution, wherein the first predetermined speed is 1000~1200 rpm and the predetermined volume is 5~10 mL; The first preparative solution is centrifuged at a second predetermined speed for a first predetermined time to obtain a precipitate, wherein the second predetermined speed is 7000~8000 rpm and the first predetermined time is 3~5 min; The precipitate is washed with a washing solvent and centrifuged at a third predetermined speed for a second predetermined time to obtain the modified solution. The washing solvent includes toluene and ethyl acetate. The third predetermined speed is 4000~8000 rpm and the second predetermined time is 3~5 min.
14. The method for preparing a perovskite solar cell according to claim 11, characterized in that, The modification solution is spin-coated onto the surface of the perovskite light-absorbing layer on the side away from the electron transport layer, and then annealed to obtain the interface modification layer, comprising: The modification solution is spin-coated onto the surface of the perovskite light-absorbing layer away from the electron transport layer at a fourth predetermined rotation speed and for a third predetermined duration, wherein the fourth predetermined rotation speed is 1000~2000 rps and the third predetermined duration is 15~30s; Annealing is performed at a predetermined temperature and continued for a fourth predetermined duration, wherein the predetermined temperature is 150~200℃ and the fourth predetermined duration is 8~10min.